Development of a mathematical model of the process of biological treatment of gaseous emissions - Бахарєва, Ганна Юріївна; Шестопалов, Олексій Валерійович; Філенко, Олеся Миколаївна; Тихомирова, Тетяна Сергіївна (Eastern-European Journal of Enterprise Technologies, 2015)
In experimental studies, the kinetic characteristics of methane oxidation by the immobilized microbial association in gaseous emissions were determined. The obtained quantitative values of specific oxidation rate of CH4 indicate a technological possibility of using the fluidized-bed bioreactor as the stage of the installation, designed for treatment of gaseous emissions from methane in drainage networks. It was found that the oxidation rate of CH4 varied from 60 ml/g·h in the region of minimum concentrations of CH4 in the medium to a maximum value of 260 ml/g·h. The presence of dependence of the specific oxidation rate of methane on its concentration in air was revealed. Based on experimental studies, a mathematical description of the processes occurring in the reactor due to changes in the concentration of incoming pollutants was developed. It was found that persistent cyclic changes in the concentration at the bioreactor inlet will lead to the persistent cycle of changes in the pollution concentration at the outlet. The results of checking calculations show the transformation of fairly smooth concentration variations of the methane at the bioreactor inlet into dramatic changes in its concentration at the end of the biotreatment process, consideration of which is necessary in designing gas-treatment equipment.